2019
DOI: 10.1080/1463922x.2019.1680763
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained design: improving multitasking with in-vehicle information systems through enhanced situation awareness

Abstract: In the age of information, in-vehicle multitasking is inevitable. The popularity of the automobile in combination with the demands of everyday life presents a demand to do more than simply focus on the road. Situation Awareness (SA) is a theory that allows designers to understand how operators interact in dynamic, complex environments. Unconstrained Design is proposed as a way of enhancing multitasking performance in-vehicle. This paper presents an experimental investigation into human-machine interface concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Another option is to use some other distraction detection algorithm as ground truth. The original AttenD algorithm has actually been used as ground truth of distraction [57] as well as for attention management [58]. This approach does not really solve the ground truth issue though, and it hampers further developments in the field, since it is impossible to be better than the "ground truth".…”
Section: E Discussionmentioning
confidence: 99%
“…Another option is to use some other distraction detection algorithm as ground truth. The original AttenD algorithm has actually been used as ground truth of distraction [57] as well as for attention management [58]. This approach does not really solve the ground truth issue though, and it hampers further developments in the field, since it is impossible to be better than the "ground truth".…”
Section: E Discussionmentioning
confidence: 99%
“…Although alone it cannot guarantee successful decision making, SA does support the necessary input processes (e.g., cue recognition, situation assessment, prediction) upon which good decisions are based. Numerous studies have highlighted the vital role of SA to ensure successful performance in complex domains (e.g., Artman, 2000;Endsley, 1993;Furniss & Blandford, 2006;Sharma et al, 2019;Skrypchuk et al, 2020).…”
Section: Loss Of Situational Awareness During Commercialmentioning
confidence: 99%
“…A significant body of research has examined the impact of HUD use on driver behaviors, particularly compared to traditional (head-down) displays. HUDs have been associated with improved lateral driving performance (Bolton et al, 2015;Horrey & Wickens, 2004a), longitudinal driving performance (Bolton et al, 2015), improved navigation (Bolton et al, 2015), spatial awareness (Tang et al, 2003), situational awareness (H. Kim et al, 2013;Skrypchuk et al, 2020), and lower self-reported mental workload (Häuslschmid et al, 2015;Liu & Wen, 2004;Smith, Streeter, et al, 2015). In addition, HUD use has been associated with faster response time for secondary tasks (Smith, Streeter, et al, 2015) as compared to traditional displays.…”
Section: Introductionmentioning
confidence: 99%